Sepsis in PD-1 light - Monneret, Guillaume (Crit Care, 2016)
Increasing evidence suggests that after the first pro-inflammatory hours, sepsis is characterized by the occurrence of severe immunosuppression. Several mechanisms have been reported to participate in sepsis-induced immune alterations affecting both innate and adaptive immunity. Of these, the concept of ‘cell exhaustion’ has gained a lot of interest because some parallels can be drawn with the cancer field in which immunostimulation approaches through blocking immune checkpoints currently obtain remarkable success. Herein, perspectives regarding co-inhibitory receptors’ contribution to lymphocyte exhaustion in sepsis will be discussed in the context of a recently published study investigating the potential of PD-1 molecule expression (i.e. PD-1 on lymphocytes, PD-L1 on monocytes) to predict mortality in septic shock patients.